Proceedings of fifteenth annual IEEE conference on computational complexity - IEEE Computer Society Technical Committee on Mathematical Foundations of Computing; IEEE conference on computational complexity (4-7 Jul 2000: Florence, Italy); ACM SIGACT; EATCS (Los Alamitos, California : IEEE Computer Society, 2000)
This volume includes 30 papers presented at the July 2000 conference. All areas of computational complexity are examined, including time-space tradeoffs and lower bounds, phase transitions, the SAT problem, PSPACE-completion, determinism, and Kolmogorov complexity.
Keywords: Computational complexity -- Congresses; Nonlinear boundary value problems -- Congresses; Polynomials -- Congresses; Isomorphisms (Mathematics) -- Congresses; Computers -- Circuits -- Congresses